mer-[RuCl3(P-P)H2O] (P-P=dppb or diop) as a starting material for the synthesis of binuclear complexes. Crystallographic structures of [(dppb)ClRu-mu(Cl)(3)-RuCl(dppb)] and [(eta(6)-C6H6)Ru-mu(Cl)(3)-RuCl(dppb)]. Imine hydrogenation using mono- and binuclear ruthenium complexes - de Araujo, M. P.; Valle, EMA; Ellena, J.; Castellano, E. E.; dos Santos, E. N.; Batista, A. A. (Elsevier B.V., 2004)
The reactivity of the mer-[RuCl3(dppb)H2O] complex (1) with di-hydrogen shows that the products formed depend on the conditions of the reaction, i.e., solvents and presence or absence of a base. The new mixed-valence complexes [(diop)ClRu-(h-Cl)(3)-RuCl(dppb)] (3), [(binap)CIRu-(p-Cl)(3)-RuCl(dppb)] (4), [(PPh3)(2)ClRu-(mu-Cl)(3)-RuCl(dppb)] (6), [(dppn)ClRu-(mu-Cl)(3)-RuCl(dppb)] (7), [(P-ptol(3))(2)ClRu-(mu-Cl)(3)-RuCl(dppb)] (8), [(SbPh3)(2)ClRu-(mu-Cl)(3)-RuCl(dppb)] (9), [(eta(6)-C6H6)Ru-(mu-Cl)(3)-RuCl(dppb)] (11) and the known mixed-valence [(dppb)CIRu-(mu-Cl)(3)-RuCl(dppb)] (5) and [(diop)ClRu-(mu-Cl)(3)-RuCl(diop)] (10) were synthesized from complexes (1) or (2) using a methodology developed in our research group. The known complexes [(dppb)ClRu-(mu-Cl)(2)-RuCl(dppb)] (12), [(dppb)(CO)Ru-(mu-Cl)(3)-RuCl(dppb)] (13) and [H2NEt2][(dppb)ClRu-(mu-Cl)(3)-RuCl(dppb)] (14) were synthesized by changing the reaction conditions between mer-[RuCl3(dppb)H2O] (1) and dihydrogen. The crystal structures of (5) and (11) were determined by single-crystal X-ray diffraction. Some of the complexes described here are effective pre-catalysts for the hydrogenation of imines. Preliminary results on the homogeneous hydrogenation of the imines Ph-CH2-N=CH-Ph and Ph-N=CH-Ph are presented. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: mixed valent Ru(II)/Ru(III) complexes; binuclear ruthenium complexes; catalysis; imine hydrogenation